Comparative Evaluation of Phytoremediation Potential of Indian Mustard (Brassica juncea) Varieties Under Sewage Irrigated Sites - V.D. Meena, M. Vassanda Coumar, J.K. Saha, N.S. Bhogal; A.K. Patra, M.L. Dotaniya*, S. Rajendiran (Journal of the Indian Society of Soil Science, 2021)
Long-term application of sewage for crop production accumulates significant amount of heavy metals in soil. Some of these metals are carcinogenic and affect the soil, plant, animal and human health adversely. Phytoremediation with mustard is a well known and regularly adopted practice for metal removal from contaminated areas. However, genetic potential of mustard cultivars may have much influence on phytoremediation potential of mustard. For this, four prominent mustard crop varieties (NRC DR 2, NRC HB 101, RH 749 and RH 119) were grown at sewage contributed metal contaminated agriculture fields of Islamnagar and Bheropura villages. Results showed that all the mustard varieties removed significant amount of Cu, Cd, Pb, Cr, Ni, Zn and Mn from soil. Mean data of all three locations showed that maximum removal of Cu (479 mg plant-1), Cd (2.80 mg plant-1), Cr (38.1 mg plant-1), Ni (9.96 mg plant-1), Zn (26.6 mg plant-1) and Mn (538 mg plant-1) was in NRC HB 101 except for Pb uptake which was highest in NRC DR 2 (1.53 mg plant-1). The NRC HB 101 showed higher phytoextraction potential compared to rest of the varieties. These results are very much useful for formulation of phytoremediation management strategies under metal contaminated agriculture areas.